2017
DOI: 10.1007/s13205-017-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and polyphenolic content in terrestrial cyanobacteria

Abstract: Cell-free extracts of twenty terrestrial cyanobacteria were evaluated for their antioxidant properties in terms of free-radical scavenging (DPPH and ABTS) and metal chelating activity and deoxyribose protection. Extract of Anabaena constricta was the most prominent antioxidant agent (IC 50 for DPPH activity 0.91 mg ml -1 , ABTS 0.23 mg ml -1 , deoxyribose protection 0.63 mg ml -1 and Fe ?2 -ion chelating 0.9 mg ml -1 ). The extracts of cyanobacterial species contained high quantity of total phenol and total fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 41 publications
1
39
0
1
Order By: Relevance
“…Because of their phototrophic lifestyle and constant exposure to high oxygen and radical stresses, these biota have a high capability for producing plentiful efficient protective chemicals against oxidative and radical stressors and exhibit adaptive responses to oxidative stresses by stimulating their intrinsic antioxidant defence systems based on mediator compounds, including polyphenolic substances (Babić et al 2016). Previously published data indicate that the phenolic acids and flavonoids in cyanobacterial cells may be responsible for their antioxidant properties (Singh et al 2017a), and thus a higher content of phenolics in cyanobacterial species may be presumed as an adaptation strategy of these organisms against abiotic stresses in their specific habitats. Therefore, the properties of these organisms may also include functional values such as free-radical quenching, metal chelation and ROS-scavenging activity (Singh et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their phototrophic lifestyle and constant exposure to high oxygen and radical stresses, these biota have a high capability for producing plentiful efficient protective chemicals against oxidative and radical stressors and exhibit adaptive responses to oxidative stresses by stimulating their intrinsic antioxidant defence systems based on mediator compounds, including polyphenolic substances (Babić et al 2016). Previously published data indicate that the phenolic acids and flavonoids in cyanobacterial cells may be responsible for their antioxidant properties (Singh et al 2017a), and thus a higher content of phenolics in cyanobacterial species may be presumed as an adaptation strategy of these organisms against abiotic stresses in their specific habitats. Therefore, the properties of these organisms may also include functional values such as free-radical quenching, metal chelation and ROS-scavenging activity (Singh et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published data indicate that the phenolic acids and flavonoids in cyanobacterial cells may be responsible for their antioxidant properties (Singh et al 2017a), and thus a higher content of phenolics in cyanobacterial species may be presumed as an adaptation strategy of these organisms against abiotic stresses in their specific habitats. Therefore, the properties of these organisms may also include functional values such as free-radical quenching, metal chelation and ROS-scavenging activity (Singh et al 2017a). Our evaluations are consistent with literature reports showing that metabolites such as flavonoids are involved in the defence system of cyanobacteria against adverse conditions (Singh et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This large group of compounds, many of which have probiotic properties, have been studied extensively for their role in food and health (Moon et al, 2006;Viskupciova et al, 2008). Recently, it has been shown that microalga, including cyanobacteria, contain flavonoids (Goiris et al, 2014;Singh et al, 2017). In the Baltic Sea, the blooming of microalga frequently occurs.…”
Section: Membrane Pumps and Detoxificationmentioning
confidence: 99%
“…3 Recently, several reports have described the antioxidative activities and properties of extracts derived from terrestrial and freshwater cyanobacteria. [4][5][6][7] However, the relationship between the antioxidative activities and the antioxidant-generating capacities of these cyanobacterial extracts is not fully understood. Moreover, a much needed resource for antioxidants, such as extremophilic cyanobacteria, has not yet been reported.…”
mentioning
confidence: 99%